Mean Aerodynamic Flow Field of an Impinging Jet Issuing from a Convergent Nozzle with Varying Nozzle to Plate Distance (Acceleron Aerospace Journal, 2025)
Jet impinging on a flat surface draws a lot of attention among the researchers working in the area of aerodynamics not only because of its complex flow physics, but also due to its wide range of applications. Starting from launch vehicles during lift-off to aircraft during vertical take-off and landing, jets impinge on the surfaces (inclined as well as flat surface) has wide range of applications. Due to these impingements, high thermal and pressure loads acts on the surface where jets are impinging. Besides these high acoustic levels as well as loss of lift also generates during this impingement. Numerical flow simulations are carried out using commercial CFD code to understand the flow physics of an impinging jet on a flat surface. Simulations are carried out at a nozzle pressure ratio of 5.0 with varying distance between the nozzle to plate. The results so obtained are analyzed in detail and are brought out in this paper.
Keywords: Aerodynamic Flow; Convergent Nozzle; Varying Nozzle; CFD